The role of the independent director in maintaining good corporate governance - Gona, Shingirirayi (Department of Commercial Law, 2014)
The role of the independent director is not clearly defined in most legislation around the globe. Hence, a company, through its Articles of Association or Memorandum of Incorporation, may attach any role it wishes the director to carry out. Most companies seem to entrust the independent director with three roles, which are the monitoring of managerial activities, strategy development, and ensuring that the company complies with the various companies' legislation. However, Dixion et al assert that, the independent director has largely emerged, amongst other factors, due to the need to monitor managerial activities.